Effectiveness of Pharmacist-Led Intervention for Hepatitis C Patients - A Systematic Review - Surya, Geraldo; Angelica, Angelica; Amalia, Zerra Rizki; Nisrina, Diflaa Kayla; Insani, Widya Norma (Pharmacology and Clinical Pharmacy Research, 2025)
Background: Pharmacist-led interventions, encompassing patient education, adherence monitoring, and personalized care, have emerged as a critical strategy to optimize treatment outcomes in Hepatitis C (HCV) management, particularly in improving Sustained Virologic Response (SVR) and mitigating drug-related challenges.Objective: This review assesses the impact of pharmacist-led interventions on key HCV patient outcomes, including SVR rates, medication adherence, and the management of Adverse Drug Reactions (ADRs) and Drug-Drug Interactions (DDIs).Methods: A systematic search was conducted on PubMed database for studies published between January 2000 and December 2024, following PRISMA guidelines. The search included Randomized Controlled Trials (RCTs), cohort, and retrospective studies. An initial search identified 192 records, from which 12 studies were included in the review. Result: In hepatitis C management, pharmacists intervened in many ways including direct close monitoring, patient education, and individualized care which led to enhanced clinical outcomes and improved patient engagement. Most included studies, both RCTs and Observational studies showcased high SVR rates. Some studies that demonstrated lower SVR rates or did not differ significantly from the control group were due to more complex patient demographics.  Recorded improvements also included medication adherence, patient engagement, and effective management of ADRs and DDIs. Conclusion: The findings indicate that pharmacist-led interventions demonstrated predominantly positive impacts on clinical outcomes. However, the evidence is limited by variations in study design and shortage of RCTs. Further research with standardized protocols is recommended to better define the role of pharmacists in HCV care.